Quantum-chemical study of carborane(12) rearrangement mechanisms - A. Yu. Shkulipa; S. P. Knyazev; E. G. Gordeev; A. D. Kirilin (Тонкие химические технологии, 2013)
The search and analysis of the ground state, intermediate and transition states of carborane(12) thermal isomerization was performed by means of quantum-chemistry methods using B3LYP/6-311+G(d,p) and M062X/6-311+G(d,p) functionals. The framework rearrangement mechanisms such as the triangular face rotation, the pentagonal pyramid rotation, as well as mechanisms via cubeoctahedral and anticubeoctahedral transition states were studied.